Practical guidelines for standardising the measurement of resting metabolism by indirect calorimetry: a literature review - A. G. Antonov; V. D. Vybornov; M. Y. Balandin; P. D. Rybakova; V. A. Badtieva; D. B. Nikityuk (National Electronic Information Consortium (NEICON), 2023)
Accurate resting metabolic rate readings are essential for dietary planning and body composition monitoring not only for healthy individuals but also for athletes. A number of factors can alter resting metabolic rate during its measurement by indirect calorimetry. The methodology used may affect the results of the study. A clear standardisation of this procedure is needed to obtain the most accurate results.Purpose: To review the literature to determine the optimal subject condition and methodology for the resting metabolism measurement procedure using indirect calorimetry.Materials and methods: A literature search was conducted in PubMed, MEDLINE and Cochrane Library databases. The query included key words and logical phrases: "calorimetry", "indirect calorimetry", "resting metabolic rate", "energy metabolism", "basal metabolism", "standards". Only Englishlanguage studies and human studies were considered. Additional information was identified because of the review and included in the review.Results: the parameters of standardization during the resting metabolism measurement procedure are described: consumption of food, ethanol, caffeine, nicotine; daily activities and physical activity; body position in space and environmental conditions during the measurement; actions of the specialist performing the procedure, etc. The article outlines effective methods for measuring resting metabolism to obtain the most accurate results in both athletes and non-athletes.Conclusion: an attempt has been made to formulate precise methodological rules for standardization and recommendations for measuring resting metabolism by indirect calorimetry.